MAINTENANCE OF PROFESSIONAL ETHICS IN A NIGERIAN HIGHER INSTITUTION OF LEARNING: STAKEHOLDERS VIEWS ON THE BEST PRACTICES - Adeyemi, B. A.; OBADIORA, Adebayo Joseph (Advances in Social Sciences Research Journal, 2020)
The study assessed the level of maintenance of professional ethics as perceived by the stakeholders among the University staff members in a Nigerian University System. It also determined the perceived loopholes in the enforcement process of professional ethics in the study area and examined stakeholders’ suggested best practices in the maintenance of professional ethics in the university system and finally determined the difference in the level of enforcement of professional ethics as perceived by the academic and non-academic staff in the study area. The study employed descriptive survey research design. The sample size was made up of 150 academic staffs and 100 non-academic staff that were selected using simple random sampling technique. An instrument titled: Professional Ethics Questionnaire (PEQ) was used to collect data for the study. Data collected were analyzed using mean, standard deviation, and t-test statistics. The results among others showed that stakeholders were found to have low level of enforcement of professional ethics. Also, there was no significant difference in the academic and non-academic staff assessment of the enforcement of professional ethics (t (248) =0.191; p>0.05) in the study area. The study concluded that religious affiliations depict a major perceived loophole in the enforcement process of professional ethics in the Nigerian Universities System.